Can a racial justice frame help overcome opposition to automated traffic enforcement?. (June 2022) - Ralph, Kelcie; Barajas, Jesus M.; Johnson-Rodriguez, Angela; Delbosc, Alexa; Muir, Carlyn
Highlights: Some advocates suggest traffic enforcement cameras may reduce racial profiling. Can using a racial justice frame increase public support for cameras? Yes. Results are from a survey experiment with a representative sample of U.S. adults. Is there backlash? Apparently not, but the frame was not effective for all groups. Messaging frames can influence public support for controversial policies. Abstract: Traffic safety cameras are used infrequently in the United States due to perceived public opposition. While efforts to increase public acceptance have traditionally focused on safety benefits, this paper explores an alternative approach. Recently, automated enforcement has attracted new supporters who see traffic cameras as a way to reduce racial profiling and minimize violent encounters between police and the public. Can we increase public support for cameras by framing them as a tool for reducing interpersonal racial bias? Is there a risk of backlash among some groups (e.g., white, conservative, and those who approve of racial profiling)? We answer these questions using a survey experiment with a representative sample of the U.S. public. We find that an interpersonal racial justice frame increases stated support for cameras (OR: 1.88, 95% CI: 1.11–3.18) and that this result persists when controlling for personal characteristics, political ideology, and views on policing. This racial justice frame did not result in backlash, although it was ineffective for some groups. Finally, we draw on rich written responses from 415 respondents to characterize views on cameras and policing. Ultimately, we find that a racial justice frame may be a useful addition to the advocate's toolkit.